Adaptation measures for seawalls to withstand sea-level rise. (15th April 2022) - Kisacik, Dogan; Tarakcioglu, Gulizar Ozyurt; Cappietti, Lorenzo
Abstract: Sea level rise necessitates adaptation measures for coastal protection structures like seawalls as changes in the design conditions will generate higher wave overtopping discharges and coastal flooding. Although increasing crest height is a common measure, the recreational function of urban seawalls limits the applicability. In this paper, performance on overtopping control of crest modifications such as storm walls, parapets, promenade, and stilling wave basin (SWB), are studied for simple and composite vertical seawalls. Two independent physical model studies from Turkey and Italy that cover a wide range of hydrodynamic conditions focusing on low relative freeboard are presented. Reduction factors that can be integrated into EurOtop prediction formulae (2018) are proposed within the experiment boundaries. The results show that a simple promenade, extending landward of a vertical seawall, provides very little reduction, whereas a seaward storm wall, under low freeboard conditions, is not effective as a similar storm wall once located on the landward edge of the promenade. Parapets decrease the overtopping further, however, the increase in relative freeboard influences the effect of parapets. Basin width and storm wall heights are important design parameters for SWB. Although the performance of different SWB configurations converges to lower reduction factors as the relative freeboard decreases, they perform better overall. Further analysis showed that the multiplication of the two individual reduction factors, one for the parapet effects and one for the promenade effects could provide an accurate representation of the composite reduction factor to determine the total effect. However, for complex geometries, it is seen that the composite reduction factors should reflect the interdependency of components when different elements with different mechanisms that change the overtopping discharge exist such as an overtopping bore on the promenade overtopping a storm wall. However, for developing future design guidelines, it is also important to consider the influence of individual components on the composite reduction factors such as the influence of storm wall height for a storm wall at the end of a promenade. Highlights: Wave overtopping over a vertical wall with different crest modifications are tested. Reduction factors that can be integrated into EurOtop prediction formulae (2018) are proposed. Crest modifications such as storm walls, parapets, promenade, and stilling wave basin (SWB), are studied. Two independent physical model studies from Turkey and Italy are presented.